Gerakan Pencegahan Stunting Melalui Edukasi pada masyarakat di Desa Bidok Kecamatan Ulim Kabupaten Pidie Jaya - Hafni Zahara; Pasyamei Rembune Kala; Futry Maysura; Nur Najikhah; Aulia Rahmadani; Marlinda Marlinda; Nurhadia Nurhadia (Nusantara: Jurnal Pengabdian kepada Masyarakat, 2025)
Stunting is a chronic nutritional problem resulting from a lack of nutritional intake over a long period, resulting in impaired growth in children. The cause of stunting is not only due to nutritional factors, namely not just a lack of food and health problems, but also due to parenting patterns. Good maternal knowledge of nutrition can prevent stunting in children. Community service activities were carried out in Bidok village, Ulim District, there were around 25 participants. This counseling lasted approximately 40 minutes, namely a presentation of the material and continued with a question and answer session with the counseling participants regarding Stunting. It is recommended to the public, especially mothers, to maintain nutritional intake during pregnancy, at birth and when children are before 2 years old to prevent stunting.